Smart Strategies and Technologies for Sustainability and Biodiversity in Herbaceous and Horticultural Crops (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Current trends in modern farming systems are moving in the direction of technical solutions for improving the sustainability and biodiversity of agroecosystems. Innovative agronomical strategies and new technologies can help farmers reduce or eliminate chemical inputs, preserve soil and water quality, decrease exhaust and greenhouse gas emissions, prevent pollution, and lower energy demand. Sustainable management also aims to enhance biodiversity in order to lengthen the “life” of agroecosystems. Herbaceous and horticultural crops are dominant crops that can contribute to achieving this goal.This Special Issue presents contributions regarding innovative technologies, machines, and strategies for the sustainable management of herbaceous and horticultural crops, including applications in organic farming systems, conservation agriculture, integrated or non-chemical weed and pest control, cover crops and intercropping use, precision and digital farming technologies, and robotic technologies for sustainability. Moreover, this Special Issue concerns conservation agriculture, organic agriculture, cover crops, intercropping, integrated/non-chemical weed and pest control, and precision and digital agriculture for sustainability. These Special Issue is a collection of 12 papers: 5 on tree crops/orchards and 7 on herbaceous crops.